Breast carcinomas that co-express E- and P-cadherin are associated with p120-catenin cytoplasmic localisation and poor patient survival. Issue 7 (1st April 2008) - Paredes, J; Correia, A L; Ribeiro, A S; Milanezi, F; Cameselle-Teijeiro, J; Schmitt, F C
Abstract : Background: Changes in junctional catenin expression may compromise cadherin-mediated adhesion, increasing cell malignant properties such as invasive and metastatic abilities. Altered expression of α-, β-, γ- and p120-catenin has been reported to be associated with E-cadherin loss or decreased expression, in both breast carcinomas and breast cancer cell lines. Aims and Methods: To investigate the expression and subcellular localisation of p120- and β-catenin in a series of human invasive breast carcinomas, and correlate it with biological markers and clinicopathological parameters. Results: Both catenins frequently exhibited a reduced membranous or cytoplasmic staining pattern. These alterations were significantly correlated with lack of both E-cadherin and oestrogen receptor-α expression. It was possible to associate the expression of β-catenin with histological grade, tumour size and nodal status, suggesting a relevant role for this catenin as a prognostic factor. The majority of E- and P-cadherin co-expressing tumours were related to cytoplasmic expression of p120-catenin; in this group of breast carcinomas, patient survival was poor. Conclusion: Results indicate that p120-catenin cytoplasmic accumulation may play an important role in mediating the oncogenic effects derived from P-cadherin aberrant expression, including enhanced motility and invasion, particularly in tumours which maintain E-cadherin expression.